THE REFLECTION AND POETIC FUNCTIONS OF RHETORICAL DEVICES IN THE POETRY OF NODIM NAMANGONIY - Sarvinoz Qurbonova (International Journal of Literature and Language Studies, 2026)
ABSTRACT. This research paper investigates the poetic nature of the lyrical heritage of Nodim Namangoniy, one of the prominent figures of Uzbek literature and the Kokand literary environment in the late 19th and early 20th centuries. Within the framework of textual and structural analysis, the article examines the poet's mastery in employing semantic (tazod/antithesis, tanosub/harmony, talmeh/allusion, husni ta'lil/poetic etiology) and verbal (ishtiqoq/derivation, tajnis/pun, iyhom/amphiboly) rhetorical devices within his ghazals. The study reveals that while remaining faithful to the conventions of traditional Eastern poetry, Nodim Namangoniy utilized these figures of speech not merely as formal embellishments, but as a driving force to illuminate the ideological-philosophical pathos of the artwork and the psychological dynamics of the lyrical protagonist. Furthermore, the rhythmic cadence, linguistic neologisms, and the series of classical cognate words characteristic of the poet's oeuvre are evaluated in terms of their role in ensuring the structural integrity of the ghazals.